(untitled) (Bangladesh Journal of Urology, 2023)
Background: A most feared complication of transrectal prostate biopsy is post-biopsy infection and/or sepsis. Safe intraprocedural measures that complement the antibiotic prophylaxis are intrarectal povidone iodine instillation or formalin needle disinfection after every core of the biopsy. Both are more effective at preventing post-biopsy infection than performing antibiotic prophylaxis alone. Objective: To assess the effectiveness of povidone-iodine intrarectal cleaning and formalin needle disinfection to prevent infection after prostate biopsy. Methodology: This study was conducted from July 2021 to June 2022 with 90 patients who underwent prostate biopsy at NIKDU. Patients were randomized into 2 equal groups, 45 in each group, by lottery. Two groups were Group-F: Standard biopsy, where the needle is disinfected with 10% formalin after each core, and Group-P: intrarectal luminal instillation of 10 ml 10% povidone-iodine for 10 min before the biopsy. Endpoint of the study was the development of signs and symptoms of infection within 7 days of prostate biopsy. Result: In terms of age, S. PSA & prostate volume, there was no significant difference between the two group. Infective complications within 7 days of the prostate biopsy were observed in 14 patients (15.6%), 3.67 times more in Group-F patients (p=0.03), and a higher incidence of UTI (72.73%) was observed in Group-F (p=0.03) than Group- P patients. The incidence of septicemia, epididymal-orchitis, and acute prostatitis was not statistically significant between the two groups. E. coli was the predominant organism found on urine culture, followed by Klebsiella pneumoniae, Enterococcus faecalis, and proteus species. Conclusion: Along with prophylactic antibiotics, povidone iodine intrarectal cleaning is superior to formalin needle disinfection in preventing infective complications of prostate biopsy. Bangladesh J. Urol. 2022; 25(2): 80-83